Exploring Factors That Drive Nonurgent Emergency Department Use - Carina Mireles-Romo MD; Eddie Hernandez BS, BA; Isabella Choi BS; Jennifer Roh MD; Soheil Saadat MD; Shannon Toohey MD (Journal of Patient Experience)
Nonurgent emergency department (ED) visits continue to rise despite efforts to reduce ED overcrowding. This study aimed to explore factors influencing ED utilization and perceptions of alternative healthcare services among patients of nonurgent ED visits. Conducted at an academic, level-1 trauma center, the study identified nonurgent visits using the emergency severity index 5-level triage acuity scale and utilized a 3-part qualitative survey to gather data on demographics, reasons for ED visits, and perceptions of the ED, primary care physicians (PCPs), and urgent care centers (UCCs). Survey responses from 586 patients were analyzed, demonstrating common themes such as ED accessibility, physician qualifications, and the need for diagnostic testing. Although participants generally expressed satisfaction with PCPs and UCCs, the frequency of nonurgent ED visits remained high. The study suggests that many nonurgent cases could have been managed using alternative healthcare services; additionally, the findings align with existing literature and support the need for enhanced patient education on appropriate ED use and the benefits of utilizing alternative healthcare options.